Parametric Analysis of Structural Noise of Steel-Concrete Composite Slab Beams - Xiao Liu; Nan Zhang; Qikai Sun; Kunpeng Wang; Zhaozhi Wu (Shock and Vibration)
In this study, the vibration acceleration and radiation structure noise in specific points, 30 cm away from the center surface of each plate of the concrete deck, web, and flange of the steel beam, are measured via the hammering test. The test is conducted on the middle concrete deck of an 8.5 m steel-concrete composite slab beam. The accuracy of the numerical model is then carefully justified. The influence of the number of shear studs, spacing, and arrangement of ribs on the concerning results is methodically examined and discussed by employing the numerical model. In the center frequency of 10–1000 Hz, the total sound power level of the structure can be lessened by improving the concrete deck thickness as well as the number of shear studs. The reduction of the rib spacing can effectively lessen the sound power level as well. The noise reduction of the plate with rib arrangement in the midspan zone is more influential than the case with uniform layout in the whole span.